Pink brain, blue brain : how small differences grow into troublesome gaps--and what we can do about it - Eliot, Lise. (Boston : Houghton Mifflin Harcourt, 2009)
A neuroscientist shatters the myths about gender differences, arguing that the brains of boys and girls are largely shaped by how they spend their time, and offers parents and teachers concrete ways to avoid reinforcing harmful stereotypes.
Includes bibliographical references and index.
Keywords: Sex differences; Sex differences (Psychology); Developmental neurobiology